On Negative Time Preference - Marco Casari; Davide Dragone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
Survey data show that subjects positively discount both gains and losses but discount gains more heavily than losses. This holds for monetary and non-monetary outcomes.
Keywords: C91; D90; 330